A THREE-STEP STRATEGY TO DEVELOP THE INDUSTRIAL ECONOMY IN CHINA THROUGH ENTREPRENEURSHIP AND INNOVATION (ResearchJet Journal of Analysis and Inventions, 2021)
The article analyzes a three-step strategy to develop the industrial economy in China through entrepreneurship and innovation. Entrepreneurship and innovation strategies provide executives with the practical knowledge, new skills, and tools to turn strategic ideas into action.. The goal is to strengthen the protection of intellectual property rights for small and medium enterprises, more effective use of intellectual property (hereinafter referred to as IM) in business strategies and to enable firms to declare independently and provide them with more active participation in property technology standards as well as international standards.